2022
DOI: 10.3390/md20050303
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mangrove Fruit: From the Phytochemicals to Functional Food Development and the Current Progress in the Middle East

Abstract: Nowadays, the logarithmic production of existing well-known food materials is unable to keep up with the demand caused by the exponential growth of the human population in terms of the equality of access to food materials. Famous local food materials with treasury properties such as mangrove fruits are an excellent source to be listed as emerging food candidates with ethnomedicinal properties. Thus, this study reviews the nutrition content of several edible mangrove fruits and the innovation to improve the fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 190 publications
(198 reference statements)
0
11
0
Order By: Relevance
“…Previous studies also reported that R. mucronata fruits contain minerals Na, K, Ca, Fe, Mn, Cu, and Zn [31]. In addition, R. mucronata analog coffee also contains protein and fat because fresh Rhizophora fruits are also reported to have protein and fat in minor amounts [32].…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies also reported that R. mucronata fruits contain minerals Na, K, Ca, Fe, Mn, Cu, and Zn [31]. In addition, R. mucronata analog coffee also contains protein and fat because fresh Rhizophora fruits are also reported to have protein and fat in minor amounts [32].…”
Section: Resultsmentioning
confidence: 97%
“…With the increasing occurrence of multi-drug resistant bacteria, new antimicrobial compounds are the need of the hour. Mangroves produce a wide array of natural products with immense medicinal and nutritional potential (19) . In the current study, Bruguiera gymnorrhiza and Excoecaria agallocha were shown significant inhibiting activity against Staphylococcus aureus which is responsible for skin infections.…”
Section: Antimicrobial Activity Of the Plant Extractsmentioning
confidence: 99%
“…Mangrove fruit is commonly used in traditional medicine for treating asthma, bleeding, coughing, heat reduction, bleeding, intestinal parasites, hemorrhoids, sprains, swelling, and ulcers. Mangrove fruit contains fiber and bioactive compounds that can be used as antioxidants and antimicrobials (Budiyanto et al, 2022). ).…”
Section: Introductionmentioning
confidence: 99%